Cultura femenina y medios de comunicación (un tejido de complicidades) - Mercedes Charles C. (Estudios sobre las Culturas Contemporáneas)
The central subject matter of this article is the construction of the concept of the feminine, and particularly the shape it takes through the intervention of the communicative media phenomenon. The female image and role is one of subordination to man, and this happens in a generic and transclassist way; and particularly, in a classist way. Feminine roles are those of wife, mother and housewife. The media have taken charge of reinforcing these roles; there are counter proposals, though. This article proposes three relational axes between woman and the media: the message, its reception, and its imprint on the woman.